The Role of Artificial Intelligence in Encouraging Innovation and Creativity in Islamic Education - Syafitri, Aisyah; Efriyanti, Liza; Devi, Indra (Nizham Jurnal Studi Keislaman, 2024)
The purpose of this study is to explain the role of artificial intelligence in encouraging innovation and creativity in Islamic education at SMPN 2 Tigo Nagari. The method used in this study uses a qualitative method with a case study approach. The case study approach is a powerful tool for exploring a particular situation or event carefully, deeply, and in detail. This approach allows researchers to gain a better understanding of the complexity and dynamics of a phenomenon or problem in a real context. The results of this study indicate that the implementation of artificial intelligence (AI) in Islamic education at SMPN 2 Tigo Nagari has a significant impact despite being faced with several challenges. The utilization of AI in teaching the Qur'an and Hadith brought about an increase in students' understanding of Islamic teachings, with AI facilitating interactive learning and exploration of the meaning of complex verses. Nonetheless, there were a number of challenges, including ethical issues, privacy concerns, and lack of teacher engagement and understanding. The positive impacts seen involve increased student understanding, personalization of learning, stimulating creativity, and management efficiency of educational institutions. AI technologies also create engaging and interactive learning experiences, increasing student motivation. The application of Virtual Reality (VR) and Augmented Reality (AR) also enriches students' contextual experience of Islamic teachings.